NONLINEAR BEHAVIOR AND IMPERFECTION SENSITIVITY OF HYBRID THREE-LAYER COMPOSITE BEAMS USING ENERGY-BASED MECHANISM ANALYSIS (GEOMATE Journal, 2026)
This study investigates the nonlinear structural behavior and imperfection sensitivity of hybrid three-layer timber beams, which is a critical issue for slender composite members in modern timber engineering. Conventional linear beam theories are often inadequate to capture the second-order geometric effects arising under large transverse deflections. A geometrically nonlinear energy-based model is developed to describe the interaction between high-stiffness outer timber layers and a softer core material. The formulation explicitly accounts for initial geometric imperfections prescribed at the global beam level. A mechanism index, denoted as η, is introduced to quantify the relative contribution of membrane forces induced by large deflection to the overall structural response, thereby identifying the transition from bending-dominated to membrane-influenced behavior. Numerical simulations are conducted using MATLAB for beams with varying amplitudes of initial sinusoidal imperfection e0​. The results demonstrate that geometric imperfections significantly amplify membrane action, leading to an earlier onset of stiffness degradation compared with geometrically perfect beams. For relatively large imperfections, a reduction of tangent stiffness on the order of 40% is observed as the applied transverse load increases. Unlike conventional nonlinear beam studies primarily based on load–deflection comparison or full three-dimensional finite element simulations, the present work introduces an energy-based mechanism index (η) that quantitatively identifies nonlinear transition and enables derivation of serviceability-oriented knock-down factors for imperfection-sensitive composite timber beams.